Educational Reaserch Trend And Ability To Complete Thesis Students Faculty Of Engineering State University - Tuti Iriani (Jurnal Pensil : Pendidikan Teknik Sipil, 2017)
The purpose of this study is obtaining the trend of students research conducted for the past 3 years in the Educational Study Program of Faculty of Engineering UNJ and knowing students’ capability in composing their bachelor thesis. Population of this research got from all the educational topic research area from 4 departments in Faculty of Engineering UNJ particularly Educational Study Program. Purposive sampling was chosen for sampling among all education bachelor thesis topics during 2013 – 2015. Qualitative descriptive was performed as research methodology by analyzing the content systematically to all the documents as data source. Results show domination of learning media and learning outcomes becoming the trend of the students’ research area. Further, R&D and Quasi Experiment were much selected to be research methodology by the students. Problem identification ability, continuity between chapters has not indicated good relevance due to incomplete analysis or justification, usage of theory and concept, selection of research methodology and data collection object and subject, proper scientific writing and references citing should strongly be assisted by the supervisor